2000
DOI: 10.1023/a:1006457520996
|View full text |Cite
|
Sign up to set email alerts
|

Pain experienced by women attending breast cancer screening

Abstract: The purpose of this study was to evaluate the pain experience of women during mammography for breast cancer screening. Possible associations with personal and medical history, sociodemographics and/or situational factors were studied. It was also investigated whether this pain influenced the intention to return for future breast cancer screening. In the Netherlands, women between 50-75 years are invited for screening every two years. A total of 1200 participants were asked to fill up a questionnaire. The respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 19 publications
5
49
0
4
Order By: Relevance
“…Previous personal experience, anxiety and insufficient attention given by the radiographer are related to the pain experienced during mammography. [10][11][12] High pain scores may even lead to the decision to stop participating in the programme. 13 Therefore, it is important for radiographers to explain the procedure well and reassure females before and during mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Previous personal experience, anxiety and insufficient attention given by the radiographer are related to the pain experienced during mammography. [10][11][12] High pain scores may even lead to the decision to stop participating in the programme. 13 Therefore, it is important for radiographers to explain the procedure well and reassure females before and during mammography.…”
Section: Discussionmentioning
confidence: 99%
“…Data from this study had shown after years of development in breast imaging, women perception of pain during mammography still remain (Asghari and Nicholas, 2004;Keemers-Gels et al, 2000). Existence of a new imaging tool with much lesser pain may be the answer to boost up the popularity for breast health screening among women worldwide (Fass, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…These papers described the health behaviours and beliefs of women who had recently undergone breast screening, [193][194][195][196][197][198][199][200] those who had undergone screening and were recommended to have further follow-up investigations, [201][202][203][204] women who had recently undergone further investigations, and were found not to have cancer, 205 women who had previously received a false-positive screening result, necessitating a breast biopsy, and then were found to not have cancer, 206 and women who had recently not reattended for routine breast screening. 187 An additional cross-sectional survey of a random population sample (not necessarily after screening) studied the level of opinion regarding the acceptability of false-positive results in mammography.…”
Section: Health Behaviours and Health Beliefs: Descriptive Data From mentioning
confidence: 99%
“…[193][194][195][197][198][199] All of these papers reported a high proportion of women with positive intentions (89-99%). The descriptive study of women who had a recent false-positive result found the same result, with 96% of the women reporting that they would reattend for routine screening next time.…”
Section: Health Behaviours and Health Beliefs: Descriptive Data From mentioning
confidence: 99%